Fish fauna of Loagan Bunut National Park, Sarawak - Nyanti, L. (Institute of Biodiversity and Environmental Conservation, 2015)
This study aims to record the composition of the fish fauna of Loagan Bunut National Park (LBNP). Surveys on the fish fauna were carried out in June and July 2003, and March and April 2004. Sampling methods that were employed included gills net, cast net, push net, trap net locally known as selambau, and hooks and lines. In this study, a total of 71 species of fish from 21 families was recorded from the study area. In terms of the number of individuals caught, 73 percent were from the family Cyprinidae, 7.7 percent from the family Bagridae, 7.5 percent from the family Helostomatidae and 2.2 percent from the family Siluridae.